Communication System Model for the Development of Muslim Communities on the Border Between Countries - Syarifah Aminah (Khazanah Sosial, 2022)
The border area between countries is currently a government priority for development. Communication as a means of interaction to build mutual agreements between community institutions and the government is an effort to prepare a strategy to increase the resilience of the Muslim community there. This research aims to formulate alternative policies in developing Muslim communities at the border between countries for sustainable development. This research uses a case study method conducted in Temajuk Village, Kaliau Village, and Sebunga Village on the border between Sambas Regency and Malaysia. The policy analysis method uses a model simulation with a dynamic system approach. The simulation ran between the years 2020 and 2030. The simulation results show the scenario in the sub-model of the Islamic religious instructor. An alternative policy that becomes the priority in developing Muslim communities at the border between countries in Sambas Regency is to increase the number of Islamic religious instructors. This development is directed at religious and social capital. The policy alternative that becomes the second priority is training and skills for the Muslim community at the border between countries in Sambas Regency.